2021
DOI: 10.1016/j.heliyon.2021.e08561
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic activity and acute toxicity of combined extract of Andrographis paniculata, Syzygium cumini, and Caesalpinia sappan

Abstract: Andrographis paniculata , Syzygium cumini , and Caesalpinia sappan are used as traditional medicines to treat diabetes mellitus. Therefore, this study aims to examine the antidiabetic effects and the acute toxicity of combined extract (1:1:1) of A. paniculata , S. cumini , and C. sappan (ASCE). The antidiabetic effect was tested using the rats model, induced by a high-fat diet and a dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…This explains why there is minimal evidence for candidates in advanced levels of type 2 diabetes, because A. paniculata appears to confer protective effects, but does not act as an insulin replacement, rather it restores insulin sensitivity. Other studies indicated that combinations of extracts from A. paniculata and other plants, such as Momordica charantia L. [ 34 ] or Caesalpinia sappan Linn and Syzygium cumini (L.) Skeels [ 35 ] have additive or synergistic potential in treatment of diabetes in rat models.…”
Section: Discussionmentioning
confidence: 99%
“…This explains why there is minimal evidence for candidates in advanced levels of type 2 diabetes, because A. paniculata appears to confer protective effects, but does not act as an insulin replacement, rather it restores insulin sensitivity. Other studies indicated that combinations of extracts from A. paniculata and other plants, such as Momordica charantia L. [ 34 ] or Caesalpinia sappan Linn and Syzygium cumini (L.) Skeels [ 35 ] have additive or synergistic potential in treatment of diabetes in rat models.…”
Section: Discussionmentioning
confidence: 99%
“…Cumini é uma árvore nativa da Índia difundida em todo o mundo, usada como antidiabético, onde todas as partes da planta contem polifenóis, e quercetina nas folhas, a M. Sphaerocarpa também utilizada na medicina popular para o controle do diabetes revelam grande quantidade de compostos fenólicos, dentre esses compostos, destacam-se o ácido clorogênico (MASAENAH et al, 2021).…”
Section: )unclassified
“…The extraction process was the same as the previous study 11 and was done by LIPI. Each 500 g of dried powder of Andrographis paniculata herbs, Syzygium cumini leaves and Caesalpinia sappan wood was extracted by maceration process using 70% ethanol.…”
Section: Extractionmentioning
confidence: 99%
“…9,10 Previous in vivo studies showed that after seven days, the rats treated by combined extract (1:1:1) with a dose of 150 mg/kg body weight significantly reduced levels of fasting blood sugar, cholesterol levels, and low-density lipoprotein (LDL) levels. 11 Some previous studies also had worked on in vitro assay. Based on those studies, all extracts have potential antidiabetic activity as an alpha-glucosidase inhibitor.…”
Section: Introductionmentioning
confidence: 99%